Optimized algorithm of auxiliary drainage scheme in tailings reservoir rainfall prediction: illustrated with a case study - Mei, Guodong; Wang, Sha; Guo, Lijie (Frontiers in Earth Science, 2023)
This study investigated the calculation algorithm of two combined schemes of lowering the coverplate of tailing ponds and installing additional drainage pumps to determine the recommended scheme of auxiliary drainage measures for tailing ponds under forecast rainfall and proposed the corresponding prediction and calculation method based on the basic data of the water level-reservoir capacity curve of tailing ponds, forecast rainfall parameters, and flood discharge system parameters. The results showed that compared with the precise algorithm, the optimized algorithm does not need to call the main procedure of flood regulation calculation and is of high calculation efficiency and accuracy. Through the optimized algorithm, the recommended auxiliary drainage scheme for forecast rainfall can be obtained quickly, which can effectively guide tailing pond flood control and drainage during the flood season.